1976
DOI: 10.1115/1.3452819
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Capacity and Surface Fatigue Life for Spur and Helical Gears

Abstract: A mathematical model for surface fatigue life of gear, pinion, or entire meshing gear train is given. The theory is based on the statistical approach used by Lundberg and Palmgren for rolling-element bearings. Also equations are presented which give the dynamic capacity of the gear set. The dynamic capacity is the transmitted tangential load which gives a 90 percent probability of survival of the gear set for one million pinion revolutions. The analytical results were compared with test data for a set of AISI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Different models and methods have been applied to pitting analyses of gears in recent years. Coy et al [8] applied the Lundberg-Palmgren model [9] to analyze the dynamic capacity and surface fatigue life of spur and helical gears. Keer et al [10,11] analyzed subsurface and surface cracking due to Hertzian contact and suggested a pitting model for rolling contact fatigue using a half-space condition, Hertzian stress theory and the body force method in conjunction with a Paris law (2D fracture mechanics).…”
Section: Introductionmentioning
confidence: 99%
“…Different models and methods have been applied to pitting analyses of gears in recent years. Coy et al [8] applied the Lundberg-Palmgren model [9] to analyze the dynamic capacity and surface fatigue life of spur and helical gears. Keer et al [10,11] analyzed subsurface and surface cracking due to Hertzian contact and suggested a pitting model for rolling contact fatigue using a half-space condition, Hertzian stress theory and the body force method in conjunction with a Paris law (2D fracture mechanics).…”
Section: Introductionmentioning
confidence: 99%
“…The value for C t can be determined by using equation (8), where B is a material constant that is based on experimental data and is approximately equal to 1.39×10 8 when calculating C t in SI units (Newtons and meters) and is 21,800 in English units (pounds and inches) for AISI 9310 steel spur gears; f is the tooth width; and ρ is the curvature sum at the start of single-tooth contact. The G L 10 life of the gear (all teeth) in millions of input shaft revolutions at which 90 percent will survive can be determined from equation (5) or (6) where N is the total number of teeth on the gear, e G is the Weibull slope for the gear and is assumed to be 2.5 (from (ref. 24)), and k is the number of load (stress) cycles on a gear tooth per input shaft revolution.…”
Section: Gear Life Analysismentioning
confidence: 99%
“…The top signs (-in eq. (8) and + in eq. (9)) are valid for right hand spiral pinion gear rotating clockwise (looking at the pinion from the side opposite the apex), or a left hand spiral rotating counterclockwise.…”
Section: Component Loadingmentioning
confidence: 99%